Peningkatan Praktik Mandiri Ibu dalam Pemantauan Status Gizi Balita melalui Pendampingan Aktivitis Dasa Wisma - S.A, Nugraheni; Aruben, Ronny; Prihatin, Ike Johan; Sari, Sari; Sulistyowati, Etik (Media Kesehatan Masyarakat Indonesia, 2018)
The incidence of malnutrition in Indonesia, also in Central Java and Semarang is still high, another problem is the lack of awareness and knowledge of the community including mother on monitoring nutritional status, and there has never been a group of community members who care about nutrition. The aim of this study was toanalyze changes in maternal attitudes and practices related to child nutrition after Dasawisma’s assistance. The research was carried out in the work area of the Tlogosari Wetan Health Center in Semarang, on the grounds that the Puskesmas area has a number of Dasa Wisma that have been arranged and also have quite a number of cases of malnutrition and malnutrition in the last few years, namely between 2.3 to 3.2% of total under five.. This research was a quasi-experimental study, with a pre and post test one group design. The subjects of the study were 110 mothers of toddlers in 35 Dawis work areas, who were selected purposively, the Dawis were provided with a weight-bearing tool and a height gauge. The results showed differences in knowledge and practice regarding infant nutrition, after being accompanied by Dawis for 1 month (p<0.05), with wilcoxon match paired test. This research can be used as evidence based practice on the proposed new program in the field of health, Dawis’s assistance as a program in monitoring the nutritional status of children.